Welfare and vulnerability: Findings from the second round of the Myanmar Household Welfare Survey (April – June 2022) - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
The second round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was implemented between April and June 2022. It follows from a first round that was carried out between December 2021 and February 2022. This report discusses the findings from the second round related to shocks, livelihoods, coping strategies and food security. We find that 19.6 percent of households reported security and climatic shocks in the three months prior to their interview. Further, there is an uptick in reported crime, violence, and insecurity across communities in the second round, compared with the first. Theft is also an important issue, with 3.2 percent of households burglarized. Fifty-five percent of households report a lower income in the beginning of 2022 compared to 12 months earlier. Eighty-three percent of households use at least one coping strategy to meet daily needs during the month prior to the survey. The three most common copying strategies are spending savings, reducing nonfood expenditure, and reducing food expenditure. Seventeen percent of households have poor or borderline food consumption, more than in round one (R1), when the share was 9.4 percent. This change is in part driven by a decrease in animal-sourced food consumption, from 5.0 days a week in R1, to 3.9 days a week in round two (R2). Finally, hunger is an issue for 4.0 percent of households. Regression analysis reveals that self-reported community insecurity and climatic shocks are strongly associated with negative outcomes for income, coping, and food security. Finally, households in Kayah and Chin are the most vulnerable; they report insecurity, violence, and crime in their communities and compared to the other states/regions are more likely to have income loss, poor food consumption and hunger.